Field reports form for submitting seasonal observations of Iowa birds, Robert K. Myers, fall 1987 - Myers, Robert K.et al (1987)
Fall report of birds and locations contributed by Robert K. Myers. Also included are details on several unusual sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed